Communicable Diseases Intelligence volume 14 issue 22 - 5 November 1990 - whole issue - No author listed (Communicable Diseases Intelligence, 1990)
Whole-issue pdf, comprising: Viruses, Chlamydias, Coxiellas, Rickettsias and Mycoplasmas Reporting Scheme Overseas briefs Original articles Reporting of notifiable diseases surveillance data - Commentary on responses to the article "Reporting of Notifiable Diseases Surveillance Data" in CDI 90/20 Epidemic Polyarthritis, Eastern Australia, Jan-Sept 1990 Flavivirus surveillance in Victoria (Sentinel Chicken Program) A recent outbreak of Dengue fever in North Queensland Arboviral surveillance - United States, 1990 Reporting Tables: Australia - Communicable Diseases Intelligence Period 11/10/1990 to 24/10/1990